Multiple interventions following an acute coronary syndrome event increase uptake into cardiac rehabilitation. (1st March 2021) - Lawless, M.; Harrison, A.S.; Doherty, P.
Abstract: Aims: Cardiac rehabilitation (CR) improves morbidity and mortality. Uptake varies for patients following acute coronary syndrome (ACS). Entry into CR is often dependent on the management strategy received, lower following percutaneous coronary intervention (PCI), higher following coronary artery bypass grafting (CABG). This study sought to investigate differences in CR uptake following an ACS event for those patients receiving multiple treatments. Methods: Data was from the National Audit of CR between 2016 and 2019. Patients with ACS were categorised as: no intervention; one treatment (such as any PCI, CABG, any valve surgery and any device therapy); two treatments; or three or more treatments. Baseline demographics and logistic regression were used to analyse the effect of multiple treatment intervention on uptake into CR. Results: A total of 6833 ACS patients were included in the analysis (0 treatments 2014, 1 treatment 3104, ≥2 treatments 2799). Patients who received ≥2 therapeutic interventions were more likely to be male, partnered and >2 comorbidities. Logistic regression showed a positive relationship between uptake total intervention. Similar associations were seen: being younger, male, partnered and having any comorbidity. The hospital stay, history of angina, diabetes and stroke was negatively correlated with an uptake. Conclusion: This study showed for the first time that multiple interventions following ACS is a significant predictor of uptake into CR. The findings align with recent trends with medically managed myocardial infarction uptake. Our findings identify factors associated with poor uptake to CR which should be considered as part of strategy to increase participation. Highlights: This is the first study to categorise treatment number in routine CR patients Uptake was found to be positively associated with treatment number Clinicians can better understand offering of CR and prioritise medically managed ACS patients